OCR BASED PLAYER JERSEY NUMBER IDENTIFICATION FOR GENERATING COMMENTARY FROM VIDEO - M, Prathibha; Anees, Sheena (IJRDO -Journal of Computer Science Engineering, 2015)
Commentary is the explication of a particular game or an event. In cricket, the commentary plays an important role in entertaining the viewers. Without commentary the game won’t be much effective. The system proposes a solution which is an AI based approach that generates playby-play commentary and automated color commentary from any video clip given, by extracting different features. For generating color commentary the most important feature is the player identification using the jersey numbers. Using Optical Character Recognition and with the help of pattern matching algorithm the numbers are identified. The methodologies used for the system are video processing, Human detection, Player identification and jersey number identification, Construction of stories related to game and players, matching the identified player with the story constructed, and finally generating commentary.